Mobility, Education and Employability in the European Union Inside Erasmus - Cairns, David (Springer International Publishing, 2018)
This book takes an in-depth look at the European Commission's Erasmus programme. In its current Erasmus+ format, the programme supports international exchange visits among students, trainees, volunteers and academic members of staff with a view to enhancing employability and encouraging intercultural understanding. Against the backdrop of the 30th anniversary of Erasmus, the authors explore the successes of the programme, most prominently the undergraduate exchange programme, as well as areas of on-going development, including the incorporation of short duration mobility projects focused on specific social issues into the initiative. Through integrating perspectives from authors in a number of European countries, all of whom have knowledge regarding various aspects of Erasmus, the book provides insight into the challenges facing the programme as it moves into its fourth decade. Mobility, Education and Employability in the European Union: Inside Erasmus will be of interest to students and scholars from a range of disciplines, including geography, sociology and European politics.